Breeding sites eradication program and Dengue fever incidence reduction in Tenggilis Public Health Center Surabaya: An Association Study - Evi Agustin (Universitas Airlangga, 2019)
Dengue hemorrhagic fever (DHF) is an endemic diseases in Indonesia. Incidence rates of the disease in Surabaya is reported as the highest for decades including of the area within Tenggilis Community Health Center. In the last five years, there were 273 new DHF cases notified. As the prevention for this detrimental menace, the government implemented breeding sites eradication program. This research aims to find out the association of breeding sites eradication program of covering, cleaning, burying, larvaciding, bed nets, (3M Plus) and its association with the existence of Aedes aegypti larvae index and the incidence of DHF in 2017. This research uses case control study design with The sample group was all the households in the work area of Tenggilis community health care whose family member diagnosed with. Case group diagnosis were confirmed and recorded at the Tenggilis Community Heath Care during period of April - May 2017 with total of 11 cases. The comparison group was taken using purposive sampling method within 100 meters of the observed objects' residences. The Result of fisher exact test of knowledge level about PSN showed significant positive association with p-value: 0,009. While insignificant association was reported by variable of attitude level, action level, larvae index with p-value 1,000, 0,361. and 0,387. It can be summarized that knowledge and behavior has a significant association with the incidence of DHF in 2017 in the area of Tenggilis Community Health Center (Puskesmas). However, the existence of larva has insignificant association with the incidence of dengue in 2017 in the Tenggilis Community Health Center (Puskesmas Tenggilis) Surabaya. Community empowerment is considered as alternative approach to improve community behavior in breeding sites eradication.